1982
DOI: 10.1080/0156655820290104
|View full text |Cite
|
Sign up to set email alerts
|

Psycholinguistic Training Programs: Are There Differential Treatment Effects?

Abstract: The findings of an investigation assessing the differential effects of psycholinguistic training programs are reported. Methodologically, meta-analysis, the analysis of analyses, was used to determine whether psycholinguistic training programs differentially affect the abilities measured by the Illinois Test of Psycholinguistic Abilities (ITPA). When findings were integrated by ITPA subtests, ITPA constructs, and salient study features, the training programs were found to differ with respect to improving psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Excluded from this review were less accessible meta-analyses found in books (e.g., Swanson, 1999); valuable reviews that were not meta-analyses (e.g., Bryen & Joyce, 1985;Buysse & Bailey, 1993); and studies that arguably have some bearing on MR, LD, and EBD but provided little to no information about whether students from these populations were included. Some examples of this are meta-analytic studies examining early language intervention (Scruggs, Mastropieri, Forness, & Kavale, 1988), early intervention with at-risk children (White, 1985-86;White & Casto, 1985), children's causal attributions for academic achievement (Whitley & Frieze, 1985), psycholinguistic training (Kavale, 1982c(Kavale, , 1984a, hyperactivity (Kavale, 1982a;Kavale & Forness, 1983), higher education (Kulik, Kulik, & Scwalb, 1983), or the relation of class size to achievement (Glass & Smith, 1979). Domain 3: Coding independent variables.…”
Section: Analyzing the Primary Studiesmentioning
confidence: 98%
“…Excluded from this review were less accessible meta-analyses found in books (e.g., Swanson, 1999); valuable reviews that were not meta-analyses (e.g., Bryen & Joyce, 1985;Buysse & Bailey, 1993); and studies that arguably have some bearing on MR, LD, and EBD but provided little to no information about whether students from these populations were included. Some examples of this are meta-analytic studies examining early language intervention (Scruggs, Mastropieri, Forness, & Kavale, 1988), early intervention with at-risk children (White, 1985-86;White & Casto, 1985), children's causal attributions for academic achievement (Whitley & Frieze, 1985), psycholinguistic training (Kavale, 1982c(Kavale, , 1984a, hyperactivity (Kavale, 1982a;Kavale & Forness, 1983), higher education (Kulik, Kulik, & Scwalb, 1983), or the relation of class size to achievement (Glass & Smith, 1979). Domain 3: Coding independent variables.…”
Section: Analyzing the Primary Studiesmentioning
confidence: 98%
“…Varma, McCandliss, & Schwartz, 2008). Yet as far as we know, there has not been a systematic and comprehensive review of the literature pertaining to cognitively focused instruction since Kavale's (1982) review more than a quarter century ago. Thus, we suggest that recent claims made for and against cognitively focused instruction should be regarded cautiously.…”
Section: Cognitively Focused Instructionmentioning
confidence: 99%
“…It has a well-documented and checkered history in education (cf. Arter & Jenkins, 1979; The Consortium for Evidence-Based Early Intervention Practices, 2010; Fuchs, 2006;Hammill & Larsen, 1974;Kavale, 1982). But there are three reasons to resist rejecting it out of hand.…”
Section: Limits Of Rtimentioning
confidence: 99%